Margin of Appreciation as an Indicator of Judicial Deference: Is It Applicable to Investment Arbitration?. (23rd November 2018) - Fukunaga, Yuka
Abstract: This paper is inspired by Philip Morris v. Uruguay, where the majority of the tribunal and the dissenting arbitrator diverge on whether `margin of appreciation, ' which has long been applied by the European Court of Human Rights (ECtHR), is applicable to investment arbitration. First, the paper points out that both the majority and the dissent wrongly consider `margin of appreciation' itself as a prescriptive standard of review that requires the ECtHR to accord deference, but that it is rather a description of standards of review that are provided in certain provisions of the European Convention on Human Rights (ECHR). In particular, the paper argues that it has been used as an indicator of how much deference is required by certain provisions of the ECHR under certain circumstances. Then, after discussing why it has hardly been used outside the ECtHR, the paper discusses whether it is applicable to investment arbitration.